Ecological engineering on rocky shores: grazing, predation, nutrient availability and their influence on epifaunal communities - Ndhlovu, Aldwin (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
"Ecosystem engineers modify, create/destroy habitat and directly/indirectly modulate availability of resources to other species by causing physical state changes to biotic and abiotic materials" (Jones et al, 1994, page 1). Previous studies have analysed top-down and bottom-up relationships to determine which form of regulation is key in controlling community composition. This study assessed the direct and indirect effects of top down and bottom up factors on the epifaunal communities of macro-algae. Epifauna are subject to the direct top-down effects of predation and bottom up effects of habitat availability. Habitat availability in turn experiences the direct top down effects of grazing and bottom up effects of nutrient availability due to upwelling. Grazing and upwelling may therefore have indirect effects on macro-algal epifauna. Four treatments (Procedural controls, Controls, Predator or Grazer exclusion) set out in a block design (n = 5) were monitored monthly for algal cover of the substratum for 12 months with the surface area of algal plants and epifaunal species composition and abundances assessed at the end of the experiment. The red alga Gelidium pristoides was selected as the ecosystem engineer as it is common, supports a diverse community of epiphytic animals and acts as a nursery for small epifaunal organisms. The experiment was run at two upwelling sites interspersed with two non-upwelling sites. Sites were separated on scales of 100km along approximately 500km of coastline. Dipping whole algae in dish washing liquid provided a strong relationship between their surface area and the weight of the film of dish washing liquid covering them. Surface area was strongly correlated to dry weight but neither surface area nor dry weight was correlated to algal cover of the substratum. Algal cover was influenced by the interactions of treatment with site (nested in upwelling) and upwelling. At all sites, treatments that allowed access to grazers, Grazer + and Control treatments, showed no significant differences and these two treatments had lower algal cover than Predator + and Closed treatments which did not differ from one another 3 [Grazer + = Control < Predator + = Closed]. A total of 44 epifaunal species were identified, with the predominant orders being Amphipoda and Isopoda. Primer results showed that only site had a significant effect on species composition, with sites that were further apart being more different. Site (nested in upwelling) had an effect on total epifaunal abundances when data were non-normalised. When total epifaunal abundances were normalised for algal cover of the substratum or algal surface area to provide density data, predation had no significant effect. Grazing did have a significant effect, but only when data were normalised to algal surface area, not cover, leading to the conclusion that indirect top-down factors through grazing of the sea weed are important in structuring epifaunal communities depending on how habitat availability is measured.
Keywords: Uncatalogued